Architecture for the emerging missional paradigm amomg faith communities in Botswana - In dialogue with Bosch - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2010.